Formal and Informal Language Styles Used in It’s Me Marsya Movie - Ida Ayu Putri Gita Ardiantari; Ni Wayan Supartini Ningsih (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
The purpose of this study is to analysis the style of language used by all the characters in the film